2020
DOI: 10.33714/masteb.742131
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Different Derivatives of Oliveria decumbens Improves Innate Immunity of Nile Tilapia (Oreochromis niloticus) Without Affecting Fish Growth and Blood Biochemical Parameters

Abstract: The objectives of this study were to investigate the effects of Oliveria decumbens as a medicinal herb with reported immunostimulatory potential on the growth, immunity status and health of Nile tilapia (Oreochromis niloticus). In an eight-week trial, fish (45 ± 5 g) were randomly divided into 13 treatments as follows: in 10 treatments fish were fed on diets containing 0 (control), 0.01, 0.1 and 1% of O. decumbens extract and essential oil and their 1:1 combinations. Also, in three treatments fish received pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The effect of different doses of the aerial parts EO and extract on the health status of Nile tilapia fish (O. niloticus), as the second major aquaculture species in the world, was investigated in an animal experiment by Jalali et al. [61] Overall, the results revealed that the administration of ethanolic extract at a dose of 0.01 % in the diet improved body weight, special growth rate, and total protein content with values of 139.88 %, 4.35 %, and 3.8 g/dL, respectively, whereas the dose of 0.1 % was more effective on respiratory burst activity and lysozyme activity with 0.89 % and 0.79 U/m, respectively (Table S3). Despite the fluctuation in albumin, globulin, triglyceride, cholesterol aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase enzymes levels of Nile tilapia, use of the EO and extract in diet had no negative or significant effects.…”
Section: Immuno-stimulant Activitymentioning
confidence: 99%
“…The effect of different doses of the aerial parts EO and extract on the health status of Nile tilapia fish (O. niloticus), as the second major aquaculture species in the world, was investigated in an animal experiment by Jalali et al. [61] Overall, the results revealed that the administration of ethanolic extract at a dose of 0.01 % in the diet improved body weight, special growth rate, and total protein content with values of 139.88 %, 4.35 %, and 3.8 g/dL, respectively, whereas the dose of 0.1 % was more effective on respiratory burst activity and lysozyme activity with 0.89 % and 0.79 U/m, respectively (Table S3). Despite the fluctuation in albumin, globulin, triglyceride, cholesterol aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase enzymes levels of Nile tilapia, use of the EO and extract in diet had no negative or significant effects.…”
Section: Immuno-stimulant Activitymentioning
confidence: 99%
“…Different studies have reported that herbal products have already improved the immune status of tilapia fish ( Jaali et al, 2020). Aqua-feed manufacturers hope to improve not only performance but also the immunity of cultured fish species (Hassaan et al, 2019).…”
Section: Al 2017)mentioning
confidence: 99%